PENERAPAN BRAIN BREAK TERJADWAL MENINGKATKAN KONSENTRASI DAN PRESTASI AKADEMIK SISWA MATA PELAJARAN IPAS KELAS 3 - Refanda, Farhani Rizki; Septi Yulaeha; Niswatul Mufarihah; Meggy Novitasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In the modern digital era, various distractions that disrupt students’ focus during learning pose a significant challenge. This study aims to evaluate the effectiveness of implementing scheduled brain breaks in improving the concentration and academic performance of third-grade students in Natural and Social Science subjects at SD N Sondakan 11. The research method employed was Classroom Action Research (CAR), which was conducted in two cyrcles, each consisting of phases of planning, action, observation, and reflection. The research subjects included 25 students. Data were collected through observations, tests, and questionnaires to measure students’ focus duration from an average of 5-10 minutes to 15-20 minutes and improved the average academic performance scores from 50 to 73.60. this research provides evidence that physical interventions such as brain breaks can positively contribute to enhancing students’ concentration and learning outcomes while recommending educators integrate this technique into daily teaching practices. Therefore, this study is expected to significantly contribute to the development of more effective teaching methodes athe elementary school level.